Redundancy Management Strategy for a Silicon/Silicon-Carbide Hybrid Switch-Based Modular Inverter System - Zhu, Yong; Peng, Zishun; Dai, Yuxing; Zhao, Zhenxing; Liu, Zeng; Yang, Yi (Frontiers in Energy Research, 2022)
In order to further improve the device utilization of a modular inverter system after the failure of a single inverter unit, a silicon (Si)/silicon-carbide (SiC) hybrid switch with high redundancy can be taken to achieve this goal. However, when the failure of the Si/SiC hybrid switches in the inverter unit occurs, the performance of this modular inverter adopting the fixed switching strategy (Fixed switching pattern and switching frequency) may be reduced. In this paper, a redundancy management strategy is proposed to prevent the performance of the Si/SiC hybrid switch-based modular inverter from reducing after the failure of the Si/SiC hybrid switches occurs. Taking the modular inverter system composed of two inverter units as an example, the experiment results demonstrate that compared to the healthy operating conditions, the increase of the voltage’s THD is smaller than 1.4%, and the increase of the total loss is smaller than 0.89%.